Kazenskoprocesne dokazne prepovedi v sodni praksi Evropskega sodišča za človekove pravice - Bergant, Katarina (Pravnik, 2014)
In fair criminal proceedings, the accused person and the state are equal. This can only be achieved by strict observance of procedural guarantees and rules concerning illegally obtaining and exclusion of illegally obtained evidences. If the breach of this rules is not sanctioned (the accused) person may lodge an application before the European Court of human rights (ECtHR) alleging a violation of his right of fair trial under Article 6 of the European Convention on Human Rights (ECHR). The fact is that ECHR does not directly govern the rules concerning obtaining and use of evidence. Despite the questions of admissibility of evidence in criminal proceedings are left to individual states, it is possible to discern the convention criteria of assessment of the fairness of the proceedings from the case law of ECtHR. ECtHR divided assessment in substances on the assessment on the proceedings of the obtaining the evidence and the assessment of the use of evidence. Where examines the level of violation while obtaining the evidences, where it does not examine each evidence, but the fairness of a criminal proceeding as a whole. The assessment depends also of the nature and the level of the violation of human rights done while obtaining the evidence, type or nature of evidence, respect of dependence of procedural rights, and direct or indirect manner of obtaining the evidence. Therefore, the article separately examines the case-law relating to the examination of the manner of the statements of accused and that relating to evidence obtained by secret investigative means and methods.
Keywords: človekove pravice; dokazi; Evropsko sodišče za človekove pravice; human rights; kazenski postopek; kazensko procesno pravo; mednarodna sodišča; sodna praksa